Analisis Kerentanan Pantai Pulau Bengkalis Berbasis Sistem Imformasi Geografis - Panggabean, Grace Julianti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Coastal area has an important role for the people who live nearby but it is prone to damage. The damage to the coastal area require countermeasures so that its impact can be minimised or eliminated. Prior to countermeasure, vulnerability analysis needs to be done by specifying coastal vulnerability index (CVI). This research was conducted along the northern coast of Bengkalis Island which is directly adjacent to Malacca Strait. Coastal vulnerability index is calculated with the value of the physical variables such as shoreline changes, visual observation, the length and width of the damage, the width of the green belt, lithology, wave height, tidal range, land use, and coastal slope. The required data for the research are landsat imagery, hydro-oceanography, bathymetry, and visual observation of damage. Results of anaysis showed that Simpang Ayam Village, Jangkang Village, Teluk Papal Village, Bantan Air Village, Teluk Pambang Village have very high coastal vulnerability. Sekodi Village has high coastalvulnerability. Area that has a moderate coastal vulnerability is Prapat Tunggal Village. Selat Baru Village, Teluk Kembung Luar Village, dan Teluk Lancar Village have low vulnerability.Keys word: Coastal vulnerablity Index (CVI), Landsat Imagery, Prone to damage